2021
DOI: 10.1002/advs.202103808
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte‐Gated Vertical Synapse Array based on Van Der Waals Heterostructure for Parallel Computing

Abstract: Recently, three‐terminal synaptic devices, which separate read and write terminals, have attracted significant attention because they enable nondestructive read‐out and parallel‐access for updating synaptic weights. However, owing to their structural features, it is difficult to address the relatively high device density compared with two‐terminal synaptic devices. In this study, a vertical synaptic device featuring remotely controllable weight updates via e‐field‐dependent movement of mobile ions in the ion‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…22 The process of memory formation in the brain can be facilitated through repeated rehearsals or training sessions. The transition process from short-term memory (STM) to long-term memory (LTM) was simulated by applying pulsed V G with different durations (0.1 s, 1 s, 10 s, 20 s) and pulse numbers (5,20,50,100) to the OECT artificial synaptic device under a pressure of 0.2 kPa (Figure 3d and e). The change in the steady-state channel current before and after the application of V G is defined as the memory level.…”
Section: Resultsmentioning
confidence: 99%
“…22 The process of memory formation in the brain can be facilitated through repeated rehearsals or training sessions. The transition process from short-term memory (STM) to long-term memory (LTM) was simulated by applying pulsed V G with different durations (0.1 s, 1 s, 10 s, 20 s) and pulse numbers (5,20,50,100) to the OECT artificial synaptic device under a pressure of 0.2 kPa (Figure 3d and e). The change in the steady-state channel current before and after the application of V G is defined as the memory level.…”
Section: Resultsmentioning
confidence: 99%
“…Hwang et al reported an ultra-flexible artificial synaptic array with concrete-mechanical cycling tolerance consisting of lithium silicate (LiSiO x ) with all-solid 2D MoS 2 channels (figure 5(c)) [31]. Recently, Oh et al developed an electrolyte-gated vertical synaptic array using a graphene/WS 2 heterojunction, as shown in figure 5(d) [121]. The electrolyte-gated vertical synaptic array not only highlights the advantages of lossless readout and parallel synaptic weight update of synaptic transistors but also shows the great potential of vertical transistors in crossbar arrays.…”
Section: Electrolyte-gated Field-effect Transistor (Egfet)mentioning
confidence: 99%
“…This work demonstrates the potential of building hardware neural networks for high-precision brain-like computing. Recently, Oh et al prepared an electrolyte-gated vertical synaptic array consisting of a graphene/WS 2 vdWH and an ionic gel [121]. By modulating the Fermi energy levels through ionic motion within the ion-gel weight-controlled layer, the LTP/D performance was successfully optimized.…”
Section: Neuromorphic Auditory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep hierarchical nonlinear processing of neural networks enables automatic and efficient learning of senior abstract representations in higher dimensional data, which has revolutionized the multimedia fields, such as images and videos, 41 speech and language. 42 It also plays an increasingly important role in the emerging fields of medical health and robotics. 43–45 With continuous performance improvement, neural networks are increasingly deployed in some practical industrial applications, including manufacturing, asset management, mobile phone voice assistance, autonomous driving, and so on.…”
Section: Introductionmentioning
confidence: 99%